Effects of the temperature and maturation stages on the germination of roystonea regia seeds - Pimenta, R. S. [UNESP]; Pedrinho, D. R. [UNESP]; Mazzini, R. B. [UNESP]; Batista, G. S. [UNESP]; Pivetta, K. F.L. [UNESP]; Penariol, A. P. [UNESP]; Romani, G. de N. [UNESP] (Int Soc Horticultural Science, 2013)
Roystonea regia (Kunth) O.F. Cook is largely used as ornamental. The propagation is done almost exclusively by seeds; however, there is a great variation in the germination process influenced by many factors. The objective of this work was to study the effects of the temperature and maturation stages on the germination of R. regia seeds. The experimental design was entirely randomized in a factorial arrangement 6×3 (six temperatures: constant at 20, 25, 30 and 35°C and alternated at 20-30 and 25-35°C, with a photoperiod of 12 hours; and three fruit maturation stages: brown, yellow and black), with four replications of 25 disseminules (seed with stucked endocarp) each. The disseminules had their mesocarp and exocarp were removed and shade dried. Their moisture content was determined, and then they were placed in plastic boxes (gerbox type) containing vermiculite. The disseminules, with the germinative intumescence, were daily noted until germination was steady. The germination rate and the germination speed index were calculated, and the data were submitted to the variance analysis. The means were compared by the Tukey test. It was concluded that the highest germination rate (99.7%) and germination speed were obtained by seeds from mature (black) fruits at the temperature of 35°C.
Keywords: Disseminules; Embryo dormancy; Seed propagation